Tuna’s exporting activities nowdays is still facing problem related with the stringent regulation and the complexity of sanitation program implemented in importing countries which triggers scores of rejection. This article discusses the analysis of regulation associated with seafood safety management system and tuna’s technical regulation initiated by Codex Alimentarius Comission (CAC), importing countries and Indonesia. Study was accomplished with content analysis method for seafood safety mana - Wini Trilaksani; Maria Bintang; Daniel R Monintja; M Hubeis (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
Tuna’s exporting activities nowdays is still facing problem related with the stringent regulation and the complexity of sanitation program implemented in importing countries which triggers scores of rejection. This article discusses the analysis of regulation associated with seafood safety management system and tuna’s technical regulation initiated by Codex Alimentarius Comission (CAC), importing countries and Indonesia. Study was accomplished with content analysis method for seafood safety management system regulation instigated in importing countries and Indonesia using CAC references. Scoring method was achieved in analyzing tuna end-product technical regulation covering various indicators explicitly histamine, heavy metal and microbiology. Result of content analysis which refer to elements of food quality and safety management system recomended by Codex namely determination of good food material criteria, implementation of risk analysis in identification and characterization of potential hazard, implementation of food safety control based on risk analysis outcomes and establishing guidelines for hygienic food handling show that United States dan European Union had already formularized and performed those recomendation, meanwhile Canada, Japan, China and Indonesia had yet entirely executed the regulation. In accordance with the criteria of organizational structure for National Food Control Systems, the European Union and Canada implement integrated agency system, Japan has single agency system, in the meantime Indonesia, United States and China possess multiple agency system. Scoring analysis on tunas technical regulation reveal that European Union has the strictest standard following by USA, Indonesia, Canada, Cina, Japan and Codex respectively.